PERSEPSI GURU DAN SISWA TERHADAP PENGGUNAAN PAPAN INTERAKTIF DIGITAL (PID) DALAM PEMBELAJARAN BAHASA INDONESIA KELAS V SEKOLAH DASAR - Maya Sari, Ria Indra Maya Sari; Farida Nugrahani; Muhammad Nurrochim; Sukiman; Arlandi Dwi Kuncoro; Uut Arif Rahman; Chera Widiastuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore and describe the perceptions of teachers and fifth-grade students regarding the integration of the Interactive Flat Panel (IFP) in the Indonesian language learning process. Amidst the digital transformation of education, the use of IFP is expected to improve the quality of interaction and understanding of language materials at the elementary school level. The research method used is descriptive qualitative. Data were collected through classroom observations, in-depth interviews with fifth-grade teachers, and a perception questionnaire distributed to students. Data analysis was carried out using data reduction, data presentation, and conclusion drawing techniques to provide a comprehensive overview of the device's effectiveness. The results showed that the use of DIB was highly positive because it increased the efficiency of material presentation and facilitated the visualization of abstract language concepts.